Peningkatan Mutu Abon Ikan dan Jabu Jabu Khas Desa Madello dengan Mesin Modern - Awaluddin, Sri Prilmayanti; Rasdi , Rasdi; Mubarak, Fhahri; Haijal, Ahmad; Putri, Hera Nur; Muntasir, Muntasir (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: to improve the quality and production of fish floss and jabu-jabu brand "KONYNYA" through the application of a spice grinding machine and multi-purpose drainer with a cylindrical model with a centrifugal system. Methodology: The methodology used in this devotion includes: Socialization, Training, Intervention and application of technology, Assistance and evaluation, Sustainability Results: The application of a spice grinding machine produces a smooth and homogeneous spice texture, and improves the taste of the product. The centrifugal system's multi-purpose cylindrical drainer has succeeded in reducing oil levels, thus improving the quality and hygiene of the "KONYNYA" brand of fish floss and jabu-jabu products typical of Madello Village. Conclusion: The implementation of a multi-purpose spice grinding machine and drainer with a cylinder model centrifugal system brand "KONYNYA" in Madello Village has been carried out effectively and on target. Limitations: This devotion only reached one partner, namely Konynya Madello Village. Therefore, it is necessary to involve similar partners or groups of MSME shredded producers in the local area to improve the quality of local superior products. Contribution: This devotion makes a significant contribution to increasing knowledge and skills in the production process, as well as improving quality to support local superior products. The implication of this research is increasing the competitiveness of local products in the market, which is expected to improve the welfare of local communities.